Green analysis of newly approved binary omeprazole/aspirin mixture in presence of aspirin impurity using ultra‐high‐performance liquid chromatography and thin‐layer chromatography methods. (28th October 2020) - Abdelaleem, Eglal A.; Abou El Ella, Dalal A.; Mahmoud, Alaa M.; Abdelhamid, Nessreen S.
Abstract: Two green, simple, and accurate chromatographic methods were developed and validated for the simultaneous determination of omeprazole and aspirin mixture in the presence of salicylic acid, a major impurity of aspirin. Method A is a reversed‐phase ultra‐high‐performance liquid chromatography; the separation was performed on a C18 column, with a mobile phase composed of ethanol:0.1% aqueous solution of triethylamine acidified with orthophosphoric acid (pH 3) (30:70, v/v) at 0.15 mL/min flow rate and 230 nm. Omeprazole, aspirin, and aspirin impurity retention times were 7.47, 4.40, and 5.13 min, respectively. Good linearity was achieved in the concentration ranges of 5–80, 5–85, and 3–50 μg/mL for the three mentioned components, respectively. Method B is thin‐layer chromatography (TLC) where silica gel TLC F254 plates were utilized to achieve separation using ethanol:ethyl acetate (2:8, v/v) as a developing system at 240 nm. The resulted R f values were 0.83, 0.65, and 0.23 for omeprazole, aspirin, and impurity, respectively. The concentration ranges of 0.1–3 μg/band for the three drugs showed good linearity. The proposed methods are eco‐friendly and greener when compared to the already reported method ( Microchemical Journal, 152, 104350). This is the first use of TLC method for the determination of the three drugs. International Council for Harmonization (ICH) guidelines were followed to ensure the validity of developed methods.